Orthogonal waveforms for multiradar and MIMO radar using noise radar technology - De Palo, Francesco; Galati, Gaspare (2015 Signal Processing Symposium (SPSympo), 2015)
In many radar applications, including marine, automotive and MIMO, there is a need for orthogonal transmission from different radar sets to mitigate mutual interference; the same applies to the different channels in a MIMO radar. New techniques, belonging to the cyclic algorithm family, might be used to generate orthogonal signals with, in addition, low sidelobes in their autocorrelation function in order to mitigate both interference and masking effects due to dynamic range problem. Their performance analysis is shown.